Predictive Role of F2-Isoprostanes as Biomarkers for Brain Damage after Neonatal Surgery. (8th October 2017) - Stolwijk, L. J.; Lemmers, P. M. A.; van Herwaarden, M. Y. A.; van der Zee, D. C.; van Bel, F.; Groenendaal, F.; Tataranno, M. L.; Calderisi, M.; Longini, M.; Bazzini, F.; Benders, M. J. N. L.; Buonocore, G.
Abstract : Objective. Neonates have a high risk of oxidative stress during anesthetic procedures. The predictive role of oxidative stress biomarkers on the occurrence of brain injury in the perioperative period has not been reported before. Methods. A prospective cohort study of patients requiring major surgery in the neonatal period was conducted. Biomarker levels of nonprotein-bound iron (NPBI) in plasma and F2 -isoprostane in plasma and urine before and after surgical intervention were determined. Brain injury was assessed using postoperative MRI. Results. In total, 61 neonates were included, median gestational age at 39 weeks (range 31–42) and weight at 3000 grams (1400–4400). Mild to moderate brain lesions were found in 66%. Logistic regression analysis showed a significant difference between plasma NPBI in patients with nonparenchymal injury versus no brain injury: 1.34 umol/L was identified as correlation threshold for nonparenchymal injury (sensitivity 67%, specificity 91%). In the multivariable analysis, correcting for GA, no other significant relation was found with the oxidative stress biomarkers and risk factors. Conclusion. Oxidative stress seems to occur during anaesthesia in this cohort of neonates. Plasma nonprotein-bound iron showed to be associated with nonparenchymal injury after surgery, with values of 1.34 umol/L or higher. Risk factors should be elucidated in a more homogeneous patient group.